The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1371/journal.pone.0257357
|View full text |Cite
|
Sign up to set email alerts
|

Clinical, financial and social impacts of COVID-19 and their associations with mental health for mothers and children experiencing adversity in Australia

Abstract: Background Australia has maintained low rates of SARS-COV-2 (COVID-19) infection, due to geographic location and strict public health restrictions. However, the financial and social impacts of these restrictions can negatively affect parents’ and children’s mental health. In an existing cohort of mothers recruited for their experience of adversity, this study examined: 1) families’ experiences of the COVID-19 pandemic and public health restrictions in terms of clinical exposure, financial hardship family stres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
21
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 34 publications
3
21
0
Order By: Relevance
“…For example, changes in maternal mental health during the pandemic predicted changes in young children’s adjustment (Thompson et al., 2022 ). Further, financial deprivation and prior mental health problems in both parents and children, along with pandemic‐related stressors, were associated with poorer parent and child functioning during the pandemic (Bryson et al., 2021 ; Westrupp et al., 2021 ). This study uniquely adds to this literature by examining not only the changes in both maternal and youth mental health from pre‐pandemic to early in the pandemic, but also across several months of the pandemic.…”
Section: Introductionmentioning
confidence: 99%
“…For example, changes in maternal mental health during the pandemic predicted changes in young children’s adjustment (Thompson et al., 2022 ). Further, financial deprivation and prior mental health problems in both parents and children, along with pandemic‐related stressors, were associated with poorer parent and child functioning during the pandemic (Bryson et al., 2021 ; Westrupp et al., 2021 ). This study uniquely adds to this literature by examining not only the changes in both maternal and youth mental health from pre‐pandemic to early in the pandemic, but also across several months of the pandemic.…”
Section: Introductionmentioning
confidence: 99%
“…Of those that experienced a change in employment, 25.5% reported losing their job while separated from loved ones or awaiting immigration. This result is consistent with previous research during COVID-19 (32-34), with a study in South Africa reporting job loss rates of 30% (34) and a study on mothers and children experiencing adversity in Australia reporting 27% job and income loss (32). Previous literature suggests that experiences of employment changes and high additional expenditure can increase feelings of financial distress which in turn is likely to exacerbate psychological distress (34-36).…”
Section: Discussionsupporting
confidence: 92%
“…An existing cohort of Australian mothers based in either Victoria or Tasmania with children aged between 5.9 and 7.2 years old was surveyed between May to December 2020. Of the 319 respondents, 85 reported that they had experienced job or income loss (27%), and 83 reported that a family member had experienced job or income loss (27%) (Bryson et al 2021 , p. 8). Half of the mothers (49%) chose “often” or “almost always” in response to an item asking “how difficult at home learning has made paid work/home duties for [the] mother” ( ibid , p. 8 & Table 1).…”
Section: Quantity Vs Quantity Within Locked-down Populationsmentioning
confidence: 99%